2014
DOI: 10.1089/sur.2012.077
|View full text |Cite
|
Sign up to set email alerts
|

Association of Excessive Duration of Antibiotic Therapy for Intra-Abdominal Infection with Subsequent Extra-Abdominal Infection and Death: A Study of 2,552 Consecutive Infections

Abstract: A longer duration of antibiotic therapy for IAI is associated with an increased risk of subsequent EAI and increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 15 publications
1
44
0
1
Order By: Relevance
“…Approximately 300,000 cases of appendicitis occur each year in the United States, 1 and at least twice that many cases of non-appendiceal infection require management. 2 Morbidity ranges from 5% among patients evaluated in broad observational studies 24 to close to 50% in some cohorts, such as the elderly or critically ill. 5,6 Despite the diversity of specific processes in these infections, the basic tenets of management are similar: resuscitate patients who have the systemic inflammatory response syndrome (SIRS), control the source of contamination, remove most of the infected or necrotic material, and administer antimicrobial agents to eradicate residual pathogens. 7,8 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 300,000 cases of appendicitis occur each year in the United States, 1 and at least twice that many cases of non-appendiceal infection require management. 2 Morbidity ranges from 5% among patients evaluated in broad observational studies 24 to close to 50% in some cohorts, such as the elderly or critically ill. 5,6 Despite the diversity of specific processes in these infections, the basic tenets of management are similar: resuscitate patients who have the systemic inflammatory response syndrome (SIRS), control the source of contamination, remove most of the infected or necrotic material, and administer antimicrobial agents to eradicate residual pathogens. 7,8 …”
mentioning
confidence: 99%
“…4,10,11 One reason that shortening therapy has been difficult is the 20% rate of clinically significant infectious complications after treatment. 3 These subsequent complications, however, are often due to progression of the original disease or inadequate original source control and may not be preventable with antimicrobial therapy alone.…”
mentioning
confidence: 99%
“…16 Currently, the average duration of antibiotic therapy for intraabdominal infection is 10 to 14 days. 4,10,11 The results of smaller studies of the effect of an abbreviated course of antimicrobial therapy have been published. Schein et al reported on an uncontrolled study in which 23 consecutive patients with diffuse peritonitis were assigned to receive 3 to 5 days of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 300,000 cases of appendicitis occur each year in the United States, 1 and at least twice that many cases of non-appendiceal infection require management. 2 Morbidity ranges from 5% among patients evaluated in broad observational studies [2][3][4] to close to 50% in some cohorts, such as the elderly or critically ill. 5,6 Despite the diversity of specific processes in these infections, the basic tenets of management are similar: resuscitate patients who have the systemic inflammatory response syndrome (SIRS), control the source of contamination, remove most of the infected or necrotic material, and administer antimicrobial agents to eradicate residual pathogens. 7,8 Antimicrobial therapy for the management of intraabdominal infections continues to evolve.…”
mentioning
confidence: 99%
See 1 more Smart Citation